Peran Wanita Karir dalam Pendidikan Anak - Siti Masitoh; Sofia Gussevi; Imam Tabroni (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2021)
The background of the problem: The working mother / career woman first meets the economic needs of the family, the two wives have a bachelor's degree to develop knowledge, the third can share time. The importance of this research is to know and analyze how the role of women according to their nature, Islamic views of housewives career outside the home and the role of career women in children's education. The research method uses qualitative where the data primary and secondary obtained through interviews, observation and documentation. Respondents were female teachers at SDIT Al Bina Purwakarta. The results showed that career women / teachers of SDIT Al Bina can help families in the field of economy / money income. Carry out his nature fitroh properly and correctly. Carry out its functions as a housewife, wife and teacher well, and can raise children at home properly. Can practice science, can pursue a career as a professional teacher and can play a dual role as a mother Wife and Teacher. Keywords: Career woman, Al Bina SDIT teacher